Pemikiran Nurcholis Majid dan Pengembangan Pendidikan Islam: Analisis Spirit Keislaman dan Keindonesiaan - Mukaromah, Siti (Panangkaran: Jurnal Penelitian Agama dan Masyarakat, 2020)
The rise of truth claims, radicalism, religious fundamentalism, and the demand of formalization of the khilāfah al Islāmiyah in Indonesia appears to have triggered disharmony in the society and posed threat to the stability of the state. Among the underlying factors contributing to the issue is the approach and method applied in the teaching system of Islamic Education (PAI) which tend to be doctrinal, normative, and exclusive. This has raised awareness of the need to introduce alternative approach in Islamic Education, to accommodate such discourse as multiculturalism, inclusive education based on the spirit of Islam rahmatan lil ‘ālamīn, and respecting the cultural diversity of Indonesian society. Nurcholish Madjid is one of the most prominent Indonesian scholars who actively promote new discourse in Islamic education as he introduces alternative approach and methods based on the spirit of Islam. This research focuses on Nurcholish Madjid’s thoughts on Islamic spirit and indigenous Indonesian identity, especially the extent to which his thoughts have significance in the contemporary development of Islamic Education in Indonesia. This research employs a qualitative-descriptive approach. The data is collected through documentation and reviews of relevant sources. The data analysis shows that Nurcholish Madjid has important thoughts on Islamic education which can be adopted as new approach in the system of Islamic education in Indonesia. Among his thoughts on Islamic education, based on his grand discourse of Islamic spirit and indigenous Indonesian identity, is the need to introduce new discourses of humanism, egalitarian, democratic and inclusive-pluralist within the system of Islamic education in Indonesia. [Maraknya truth claim, radikalisme, politisasi, dan fundamentalisme agama, serta wacana formalisasi syari’at negara khilāfah al Islāmiyah menyebabkan perpecahan dan mengancam stabilitas negara Indonesia. Persoalan tersebut salah satunya dilatarbelakangi oleh pembelajaran Pendidikan Agama Islam (PAI) yang bersifat doktriner, eksklusif dan normatif. Oleh sebab itu, perlu alternatif solusi melalui Pembelajaran Pendidikan Agama Islam yang multikultural, inklusif dan pluralis dengan berbasis pada spirit keislaman dengan membumikan Islam rahmatan lil ‘ālamīn dan spirit keindonesiaan yang menghargai keragaman (pluralitas). Salah satu pemikir dan cendekiawan muslim Indonesia yang aktif menyuarakan spirit keislaman dan keindonesiaan adalah Nurcholish Madjid. Dengan demikian, subjek dalam penelitian ini ialah Nurcholish Madjid mengenai konsep spirit keislaman dan keindonesiaan dan kontribusinya terhadap pengembangan Pendidikan Agama Islam. Pendekatan dalam penelitian ini menggunakan pendekatan kualitatif-deskriptif, dengan jenis penelitian kepustakaan (library research). Pengumpulan data menggunakan metode dokumentasi dengan menganalisis data berupa sumber-sumber dari berbagai literatur yang memiliki persamaan dengan tema penelitian. Hasil penelitian menunjukkan bahwa kontribusi pemikiran Nurcholish Madjid mengenai spirit keislaman dan keindonesiaan terhadap Pengembangan Pendididkan Agama Islam ialah terwujudnya pembelajaran Pendidikan Agama Islam yang humanis, egaliter, demokratis, dan inklusif-pluralis.]